Міжмовна інтерференція та шляхи її подолання при вивченні другої іноземної мови - Семенюк, Лариса Йосипівна; Semeniuk, Larysa Y. (Національний університет “Острозька академія”, 2015)
У статті проаналізовано вплив міжмовної інтерференції на ефективність оволодіння студентами другою іноземною мовою (німецькою після англійської) та окреслено шляхи подолання цього негативного впливу.

The article is devoted to the investigation of interlingual interference, and namely, its impact on the effectiveness of students’ mastering German as the second foreign language after learning English as the first foreign language. Typical mistakes caused by different types of interference such as: phonetical, grammatical, lexical, socio-cultural and others, due to overlapping the new language skills which are being formed (the German language) the existing ones (native language and English) have been considered. The ways of eliminating the negative influence of lingual and cultural interference and creating conditions for positive transference in the process of teaching German as the second foreign language have been outlined.
Cross Language Interference and ways of their OIvercoming while Studing the Second language
Keywords: міжкультурна комунікація; міжмовна інтерференція; трансференція; соціокультурна інтерференція; мовні універсалії; контрастивний підхід; лінгвістична компетенція; intercultural communication; interlingual interference; transference; socio-cultural interference; lingual universals; contrastive approach; linguistic competence